Minat Pembudayaan Permainan Tradisional Balogo di SD Negeri Bahungin - Rakhman, Muhammad Raiza; Perdinanto; Rahmadi (MAN Insan Cendekia Jambi, 2025)
This research aims to determine the extent of students' interest in cultivating the traditional game of Balogo at Bahungin State Elementary School and to evaluate the effectiveness of this game as part of Physical Education, Sports, and Health (PJOK) learning. This study employs a descriptive quantitative approach, using a closed questionnaire based on the Guttman scale to measure students' interest levels. The population of the research is all students of Bahungin State Elementary School, with a sample of 27 purposively selected fourth-grade students. Data analysis is conducted using descriptive percentage statistics to identify the interest level of students in the cultivation of the Balogo gameThe research results showed that 96% of students (26 respondents) have very high interest, while 4% of students (1 respondent) fall into the high category. There were no respondents who showed interest in the medium, low, or very low categories. These findings indicate that the Balogo game is very well received by students and can be an effective means of preserving local culture and increasing student participation in physical activities.